2017
DOI: 10.1177/0003319717742544
|View full text |Cite
|
Sign up to set email alerts
|

Carotid–Femoral Pulse Wave Velocity in the Prediction of Cardiovascular Events and Mortality: An Updated Systematic Review and Meta-Analysis

Abstract: Arterial stiffness (AS) is a predictor of coronary artery outcomes in patients with cardiovascular disease (CVD). Carotid-femoral pulse wave velocity (cf-PWV) is a commonly used method for assessing AS. This study aimed to assess the relationship between cf-PWV and clinical CVD events. Of the 786 studies identified, 19 studies were included in the final meta-analysis. Meta-analysis revealed that participants with high cf-PWV by 1 standard deviation (SD), 1 m/s, and cutoff points have a high pooled relative ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
103
2
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(130 citation statements)
references
References 44 publications
4
103
2
7
Order By: Relevance
“…for CV events. 13,15,16 To our knowledge, ours is the largest cross-sectional observational study of its kind performed in ambulatory conditions and in different high CV risk subgroups of participants. At the moment, the large num- In the whole participants of the study, ambulatory aortic BP circadian trend mimicked that of ambulatory brachial BP, though SBP was lower and DBP higher at the central than at the peripheral site.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…for CV events. 13,15,16 To our knowledge, ours is the largest cross-sectional observational study of its kind performed in ambulatory conditions and in different high CV risk subgroups of participants. At the moment, the large num- In the whole participants of the study, ambulatory aortic BP circadian trend mimicked that of ambulatory brachial BP, though SBP was lower and DBP higher at the central than at the peripheral site.…”
Section: Discussionmentioning
confidence: 99%
“…We observed a variable association between these parameters and CV risk, hence confirming and extending to the dynamic conditions of daily life the findings provided by previous studies performed at rest in standardized laboratory conditions. Such studies highlighted the predictive value of arterial stiffness and, to a relatively less extent, of measures of wave reflection and central hemodynamics, in the general population, in elderly participants, in patients with essential hypertension, diabetes mellitus, renal diseases, and CV disease, and helped acknowledge the utility of these estimates as intermediate end points for CV events …”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have presented that aortic stiffness is a marker of vascular aging and could reflect modification in mechanical wall properties responsible for vascular disease and occurrence of cardiovascular (CV) diseases . Furthermore, in daily practice, its measurement may become a main routine assessment for patients …”
Section: Introductionmentioning
confidence: 99%
“…4 Furthermore, in daily practice, its measurement may become a main routine assessment for patients. 5 One of the main reproducible methods used to determine aortic stiffness is carotid-femoral pulse wave velocity (PWV). 6 PWV is defined as the velocity of arterial pulse moving along the vessel wall.…”
Section: Introductionmentioning
confidence: 99%
“…A more recent meta‐analysis of 19 studies (n = 19 908) demonstrated a rise of 12% in future CV events for every increase in carotid‐femoral PWV by 1 m/s. These cohorts were mixed; eight of them included patients with various diseases, such as hypertension, renal failure, and renal transplant recipients, whereas the rest of them included healthy individuals …”
Section: Discussionmentioning
confidence: 99%